ASWAJA'S VALUES FRAME-BASED ACCOUNTING: A CASE STUDY AT THE NAHDLATUL ULAMA UNIVERSITY IN INDONESIA - Aida Nahar (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Accounting is a set of practices that are influenced by the world and social realities. Therefore, the values of people's beliefs are needed in its application. The problem in this study is how accounting practices are based on the Ahlussunnah Wal-Jama'ah (Aswaja) values. This study aims to construct accounting practices derived from the values of Ahlussunnah Wal-Jama'ah. This research used an interpretive paradigm and a case study approach at the Nahdlatul Ulama College. The data analysis modified the Seidel and Yin approaches. The findings of this study are the basic values of Ahlussunnah Wal-Jama'ah An-Nahdliyah have an impact on social behavior which consists of the values of I'tidal, Tawassuth, Tawazun, Tasamuh and amar ma'ruf nahi munkar. Accounting that reflects these values includes obedience to principles, conformity of the budget with work programs and strategic plans, clarity of the accounting system, use of the concept of budget deliberation, fikroh islahiyah, principle of balance, accounting markaziyah, taqiya, and honesty.